Early results of the conservative treatment of distal radius fractures-immobilization of the wrist in dorsal versus palmar flexion - Maki Grle; Miro Miljko; Ivana Grle; Faruk Hodžić; Tarik Kapidžić (Medicinski glasnik, 2017)
Aim: To evaluate immobilization with dorsal forearm plaster splint with the wrist in dorsal flexion vs palmar flexion in patients with distal radius fracture. Methods: In the prospective study (2012-2014) 122 patients (of which 22 patients lost) with fractures of the distal radius type A2, A3 and C according to the AO classification were investigated. At the end there were 50 patients in each of the two groups: the dorsiflexion (DF) group had a total of 37 women and 13 men, mean age was 63.48 ± 14.70, and in the palmar flexion (PF) group there were respectively 38/12, and the mean age was 64.20 ± 12.99. In both groups measurements of radiological, clinical and functional parameters were conducted. Patient related wrist evaluation survey (PRWE) and SF12 questionnaire were used for evaluation of pain and function of the wrist and physical and mental condition, respectively. Results: The study showed excellent results in both groups but there was significant improvement in the range of motion (ROM) on every measurement in the DF group: dorsal flexion 47.70±15.29; ulnar deviation 24.10±7.80; radial deviation 11.50±5.65 vs PF 22.80±19.04; 16.00± 9.31; 4.80± 494 (p<0.001). Also, radiological parameters showed significant improvement until the end of the follow-up. Functional parameters showed significant improvement of physical component of SF-12 in the DF group (p˂0.014). Conclusion: Immobilization with forearm plaster splint on the dorsal side and with the wrist in dorsiflexion gives better early clinical, radiological and functional results in patients with fractures of type A2, A3, C1-3 in patients of all age groups, compared to immobilization with the wrist in palmar flexion.
Keywords: wrist; distal radius fracture; conservative treatment; splints